KORELASI TINGKAT KECEMASAN DAN AKTIFITAS FISIK TERHADAP SIKLUS MENSTRUASI PADA REMAJA PUTRI - Kusumawardani, Emi; Silfiana, Andi; Wulandari, Ikrawanty Ayu; Sendra, Eny (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The physical development of adolescents is not only seen in terms of size, but also functional changes, especially in the reproductive organs. The menstrual cycle in women can be disrupted by anxiety and lack of physical activity. The purpose of the study was to determine the correlation of anxiety levels and physical activity with the menstrual cycle in adolescent girls. The research design used in this study was cross sectional. The research was conducted at 2 high schools in Palopo City in September 2023. The population was all 11th grade adolescent girls. The sample amounted to 60 respondents. The sampling technique used in this study was Simple Random Sampling. Data analysis was performed univariate and bivariate. The results showed a relationship between anxiety level (p value: 0.023) and physical activity (p value: 0.043). It is recommended to the community, especially for adolescent girls who have menstruated, to always improve their knowledge about reproductive health, especially about menstruation to reduce the level of anxiety during menstruation and know what physical activities are good to do during menstruation.Keywords: Physical Activity, Anxiety, Menstruation.